Mesenteric schwannoma: a rarity or rising trend? - Swaminathan, Subramaniam; Joseph, Jebin; Kumar, Arun (International Surgery Journal, 2019)
Schwannomas are neurogenic, benign, well circumscribed tumors arising from schwann cells. Schwann cells are neural originating cell. These are either sporadic or inherited with sporadic being most common. In about 3% of patients, association with neuro-fibromatosis 2 gene is documented. Primary mesenteric schwannoma is extremely rare with establishing a pre-operative diagnosis almost impossible. Imaging modalities including computed tomography as well as MRI fails to make a diagnosis due to the non-specific characteristics. Surgery is curative with histopathological examination and immunostaining establishing the final diagnosis post-operatively. Immunostaining helps in differentiating it from other conditions such as gastro-intestinal stromal tumors as well as malignancies. Rarity of this condition make this case report of a 32-year-old male unique.